2021
DOI: 10.3390/cells10051080
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-Associated Protein ATIP3, an Emerging Target for Personalized Medicine in Breast Cancer

Abstract: Breast cancer is the leading cause of death by malignancy among women worldwide. Clinical data and molecular characteristics of breast tumors are essential to guide clinician’s therapeutic decisions. In the new era of precision medicine, that aims at personalizing the treatment for each patient, there is urgent need to identify robust companion biomarkers for new targeted therapies. This review focuses on ATIP3, a potent anti-cancer protein encoded by candidate tumor suppressor gene MTUS1, whose expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…In breast cancer, ATIP3 was found significantly downregulated in taxane-sensitive tumors [ 28 ]. It is an interesting therapeutic target for breast cancer [ 29 ]. Caspase 2 ( CASP2 ) has been shown to cleave the Microtubule-associated protein tau (coded by the gene MAPT ) that promotes microtubule assembly and stability and potentially competes with taxanes for microtubule binding.…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer, ATIP3 was found significantly downregulated in taxane-sensitive tumors [ 28 ]. It is an interesting therapeutic target for breast cancer [ 29 ]. Caspase 2 ( CASP2 ) has been shown to cleave the Microtubule-associated protein tau (coded by the gene MAPT ) that promotes microtubule assembly and stability and potentially competes with taxanes for microtubule binding.…”
Section: Resultsmentioning
confidence: 99%
“…Several ATIPs have been discovered to interact with the H8 and C-terminal of active AT 2 R [71] , [72] . From the conformational ensemble of AT 2 R, the interface for AT 2 R and ATIP is hidden in the TM bundle center in the inactive state, preventing AT 2 R from interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Such mechanisms may involve binding to and activation of Src homology region 2 domain-containing phosphatase-1 (SHP-1) (Li J-M et al, 2007), although others suggested that the antiproliferative effect of AT 2 R/ATIP1 is mediated through ATIP1/PPARc binding and crosstalk (Kukida et al, 2016;L€ utzen et al, 2017). Recently, research has focused mainly on ATIP3, which seems to be the main isoform possessing tumor-suppressor properties through interference with microtubule depolymerization within the mitotic spindle apparatus (Haykal et al, 2021). It is currently unclear whether the AT 2 R plays any role in these anticancer effects of ATIP3 or, for that matter, ATIP1.…”
Section: A B Cmentioning
confidence: 99%
“…The anticancer effects of ATIP3 are reviewed in more detail in Section VI.H and in other reviews (Bozgeyik et al, 2017;Haykal et al, 2021).…”
Section: A B Cmentioning
confidence: 99%